(untitled) (Jagannath University Journal of Arts, 2026)
The rapid growth of technology is making it harder to tell the difference between people and machines. This problem is likely to stay. As a result, posthumanism has become an important way to rethink ideas about identity, personhood, and ethics in digital settings. This is because posthumanism has become an important point of view. Posthumanism challenges the fundamental humanist tenets that have traditionally shaped our understanding of humanity, advocating for a reassessment of the roles of artificial intelligence, robotics, and biotechnology in human existence. Posthumanism is a movement that calls for a new look at these technologies. These ideas have been the basis of our understanding of what it means to be human. The advent of artificial life, including beings that display traits like intelligence, consciousness, and free will, has initiated new ethical investigations regarding the nature of personality. These questions have come up because of the rise of artificial life. There has been a growing number of questions about these topics because artificial life is becoming more popular. This essay aims to examine the ethical ramifications of posthumanism and artificial life, particularly in relation to the potential erosion of established moral and social frameworks through the redefinition of personhood. The article will conduct a precise analysis of how these elements may constitute a threat. The essay will focus on the consequences that may result from reinterpreting the notion of personality. Jagannath University Journal of Arts, v-5, i-01, 2025: p154-159